2016
DOI: 10.1177/0091552116679731
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Students

Abstract: Objective: In an effort to break away from the stale classifications of community college students that stem from the hegemonic perspective of previous literature, this work utilizes the perceptions of community college practitioners to demonstrate new ways of understanding the identities of community college students. Method: By utilizing Gee’s identity theory and Grillo’s theory of intersectionality, we analyze interviews with community college practitioners from three different community colleges on the Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…internationalization coordinators, members of the internationalization office, and leaders of international research or service initiatives). Second, similar to Levin, Viggiano, López Damián, Morales Vázquez, and Wolf (2017), administrators in key roles of influence over institutional policy were targeted (i.e. rectors, department heads, and the like).…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…internationalization coordinators, members of the internationalization office, and leaders of international research or service initiatives). Second, similar to Levin, Viggiano, López Damián, Morales Vázquez, and Wolf (2017), administrators in key roles of influence over institutional policy were targeted (i.e. rectors, department heads, and the like).…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Negative perceptions of community colleges are well documented in the research literature; researchers often name these negative perceptions as community college stigma or transfer stigma (Alexander et al, 2009;Bowker, 2021;Gauthier, 2020;Hawk & Hill, 2016;Holland, 2015;Hyatt & Smith, 2020;Jain et al, 2017;Laanan et al, 2010;Levin et al, 2017;Reyes, 2011;Shaw et al, 2019).…”
Section: Stigma and Improving Community College Advocacymentioning
confidence: 99%
“…More recent empirical studies have found that community college engagement with faculty is a stronger predictor of learning than peer engagement (Lundberg, 2014), and that frequent interaction with faculty and counselors predicted grade point average (GPA) for Latino students (Tovar, 2015). However, not all faculty understand the diversity of identities and experiences that characterize community college students (Levin, Viggiano, López Damián, Morales Vazquez, & Wolf, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%